Analysis of vitamin C content, water content, and organoleptic test of lemon segment wall dodol - Frasiska, Nurul; Nurwidah, Andi; Salfiana, Salfiana (Anjoro: International Journal of Agriculture and Business, 2024)
Waste will become a problem if not managed properly. One way to do this is to recycle lemon waste into other products with economic value, such as making dodol from lemon segment wall. This study was conducted to determine the effect of the addition of lemon segment wall in making dodol and to determine the best treatment for making dodol. This study used a complete randomized design (CRD) with 4 treatments. The treatments used were control (without the addition of lemon segment wall), and the addition of different lemon segment walls, namely F1 (5%), F2 (10%), and F3 (15%), with each treatment repeated 3 times. Testing parameters in this study include water content, vitamin C, yield, and organoleptic test. Data from the study results were analyzed for variability to determine the effect of treatment on the test parameters. If there was a significant effect, the Duncan test was continued to determine the real difference between treatments. The results showed that making dodol with treatment F4 (addition of 15% lemon segment wall) is a treatment that has high values in each test parameter, including water content (36.52%), vitamin C (379.93%), and yield content (80.21%). Meanwhile, making dodol with treatment F0 (without the addition of lemon segment wall) is a treatment that has the lowest value in each test parameter, including water content (26.87%), vitamin C (247.94%), and yield content (79.41%) in laboratory testing and the best treatment as measured by the organoleptic test which is most liked by the panelists, namely treatment F0 (without the addition of lemon segment wall).